UJI COBA LKPD BERORIENTASI MODEL PEMBELAJARAN BERBASIS PROYEK PADA MATERI GLB DAN GLBB DI KELAS VIII SMP NEGERI 8 PEKANBARU - Wiranti, Kintan Rosa; Islami, Nur; Zulhelmi, Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: Project-based science LKPD is a teaching material that is able to provide details and clear guidance to students in order to carry out project tasks effectively and efficiently. The research objective is to develop a valid and practical project-based LKPD on GLB and GLBB materials for VIII SMP grade . The study was conducted through the validation stage 2 times. The first validation was conducted by 3 lecturers majoring in Mathematics and Natural Sciences FKIP Riau University namely Physics, Biology and Chemistry as well as 2 experienced junior high school science teachers. The second validation was conducted by 2 science teachers in class VIII of SMP Negeri 8 Pekanbaru. Furthermore, a limited test was carried out on 40 students of class VIII of SMP Negeri 8 Pekanbaru. Research instruments in the form of validation sheets, questionnaire responses of teachers and students. Analysis of research data using quantitative descriptive analysis by calculating the index of each indicator used to determine the validity and practicality of the developed LKPD. The results of the study concluded that the project-based LKPD developed on GLB and GLBB material was valid and practical and could be used in learning to support the teaching and learning process so that it became better.Keywords: LKPD, Project Based, GLB and GLBB